Effect of neonatal dentate gyrus lesion on allothetic and idiothetic navigation in rats - Czéh, B; Stuchlik, A; Wesierska, M; Cimadevilla, J M; Pokorný, J; Seress, L; Bures, J (Neurobiology of learning and memory, 2001)
Goal-directed navigation is believed to be the combined product of idiothetic and allothetic orientation. Although both navigation systems require the hippocampal formation, it is probable that different circuits implement them. Examination of Long-Evans rats with dentate gyrus lesions induced by neonatal X-ray irradiation may show the dissociation of these two components of navigation. Two recently developed place avoidance tasks on a rotating circular arena were used to test this hypothesis. In the first test, the position of the punished area is stable in the room frame but is permanently changing on the surface of the arena. This task requires the rat to use allothetic orientation and to disregard idiothetic orientation. In the second test, the prohibited area is fixed in the coordinate system of the arena and the experiment is conducted in complete darkness, forcing the rat to rely exclusively on idiothesis supported by substratal cues. The results suggest that the dentate gyrus lesion interferes less with idiothetic orientation than with allothetic orientation. In addition, an attempt was made to control the number of developing granule cells by exact timing of a single high dose of perinatal irradiation, and to measure the ensuing behavioral deficits. Rats irradiated at 6, 18, or 24 h after birth were tested as adults in the Morris water maze. Irradiated animals showed significant, but highly variable, learning deficit, but histological examination indicated that the granule cell loss did not correlate with the degree of behavioral impairment.
Keywords: Escape Reaction; Animals; novorozená zvířata; nervová síť; Brain Mapping; Appetitive Behavior; rozpomínání; Orientation; gyrus dentatus; Rats, Long-Evans; Avoidance Learning; Dentate Gyrus; úniková reakce; Animals, Newborn; orientace; Nerve Net; Mental Recall; mapování mozku; Fear; apetenční chování; strach; potkani Long-Evans; Male; učení vyhýbat se; krysa rodu Rattus; Maze Learning; zvířata; mužské pohlaví; bludiště - učení; Rats